Exploring the Impact of Financial Literacy on Entrepreneurial Intentions Among University Students - Bhardwaj, Pallavi; Sharma, Kiran; Zaidi, Sana (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study explores the impact of financial literacy on entrepreneurial intentions among university students, with a focus on moderating and mediating factors such as gender, academic background, saving behavior, and family financial socialization. Grounded in the Theory of Planned Behavior (TPB), the research posits that financial literacy influences entrepreneurial intentions through enhanced attitudes toward entrepreneurship, perceived behavioral control, and subjective norms. A quantitative, cross-sectional survey design was employed, drawing on responses from 500 university students across various disciplines in India. Key instruments included Lusardi and Mitchell’s financial literacy scale and Liñán and Chen’s Entrepreneurial Intention Questionnaire. Findings reveal a strong, positive, and statistically significant relationship between financial literacy and entrepreneurial intention (r = 0.63, p < 0.01). Regression analysis confirmed that financial literacy is a significant predictor, accounting for 39.7% of the variance in entrepreneurial intention. Academic background significantly moderated this relationship, with commerce students exhibiting a stronger link than their non-commerce peers. However, gender did not significantly moderate the relationship. The study also highlights the mediating role of saving behavior, suggesting that financial literacy not only shapes entrepreneurial intent but also supports its practical realization through financial preparation. The research underscores the importance of integrating financial literacy into university curricula across disciplines, promoting early financial education, and incorporating digital financial competencies to prepare students for entrepreneurship in a post-pandemic digital economy. The findings offer actionable insights for educators and policymakers aiming to foster youth entrepreneurship and financial inclusion.